PATRIARCHAL PRACTICES AND RESISTANCE IN ROALD DAHL’S MATILDA - Anggraeni, Erisa (LANTERN (Journal on English Language, Culture and Literature), 2017)
This thesis discusses a novel entitled Matildaby Roald Dahl. The aims of the thesis are to explain and to analyse the intrinsic and extrinsic aspects of the story. The analysis will be focused on The Wormwoods where patriarchal practice happens. The result of this thesis describes the meaning of the representation of patriarchal ideology in Matilda which is the representation of woman are considered to have lower status than men. The method used in obtaining the data is library research and additional data from the internet. With an analysis of The Wormwoods, it can be concluded that the representation of patriarchal ideology in Matilda has different impacts for each family member Wormwood and made Matilda to choose living with her teacher.